Shallots Marketing Channel Analysis (Case Study in Sekoto Village, Badas District, Kediri Regency) - Yuliafatmawati, Anisya; Mulyadi, Fadli; Inggrida, Jedda (JURNAL AGRIMENT, 2024)
Sekoto Village is the centre of shallot farming in Badas District, Kediri Regency. The fluctuation of production can affect the price of shallots on the market, even the current shallot price fluctuations tend to be high. As one of the horticultural vegetables, shallots have a long marketing chain, which can cause significant price differences between farmers and consumers. Shallot farmers in Sekoto Village still conduct traditional marketing that relies on intermediary traders. This study aims to: (1) analyse the shallot marketing channels in Sekoto Village, and (2) analyse shallot marketing efficiency in Sekoto Village. The data analysis method used is marketing channel analysis by describing the marketing institutions involved and the flow of marketing activities and marketing functions performed by marketing institutions, while the marketing efficiency analysis is done by calculating shallot marketing margin and farmer's share. The results showed that there are three marketing channels in Sekoto Village, I: farmers - retailers - consumers, II: farmers - intermediary traders - retailers - consumers, and III: farmers - out-of-region sending traders - consumers. The highest marketing margin value is in marketing channel II, which is Rp7,575, while the lowest marketing margin is in marketing channel III at Rp4,750. The most efficient marketing channel is in the marketing channel III. However, marketing channels I and II can also be said to be efficient, therefore the two marketing channels can still be an alternative shallot marketing channel in Sekoto Village.